2021
DOI: 10.1177/1052684621993115
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Anti-Black Racism in Everyday Teaching, Learning, and Leading: From Theory to Practice

Abstract: Anti-Black racism and White supremacy continue to have dire impact on the lives and educational outcomes of Black people and students in educational spaces. Examining ways in which this form of racism is disrupted, confronted, and challenged in education and schooling is important not only to Black students, scholars, practitioners, and staff, but to all People of Color. Drawing on research conducted with educators in, Canada, the United States and our lived experiences as Black educators this article examines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 36 publications
0
46
0
Order By: Relevance
“…There is scope for extending this kind of research in the English context, including how it might differentially affect learners of Black Caribbean heritage who may be more likely to manifest forms of cultural resistance in the form of rap music, hair styles or the use of dialect in the classroom. Analysis centres on the role of fear on the part of some White teachers of Black bodies, but also hostility to manifestations of Black counter‐cultures of resistance (Lopez & Jean‐Marie, 2021). Recent, careful ethnographic work in inner‐city schools in England has detailed how processes of racialisation of learners from Black backgrounds by some White teachers leads to the uneven and culturally insensitive application of behaviour management policies (Wright et al, 2020).…”
Section: The Sewell Report: a Critical Analysismentioning
confidence: 99%
“…There is scope for extending this kind of research in the English context, including how it might differentially affect learners of Black Caribbean heritage who may be more likely to manifest forms of cultural resistance in the form of rap music, hair styles or the use of dialect in the classroom. Analysis centres on the role of fear on the part of some White teachers of Black bodies, but also hostility to manifestations of Black counter‐cultures of resistance (Lopez & Jean‐Marie, 2021). Recent, careful ethnographic work in inner‐city schools in England has detailed how processes of racialisation of learners from Black backgrounds by some White teachers leads to the uneven and culturally insensitive application of behaviour management policies (Wright et al, 2020).…”
Section: The Sewell Report: a Critical Analysismentioning
confidence: 99%
“…The enduring impact of slavery in the history of humanity makes attempts to undo race and racism nearly impossible. Similar to the solidity of concrete structures, the normalisation of race and racism is solidified in human culture and is passed on through interaction actively or passively, intentionally or unintentionally, overt or otherwise (Delgado and Stefancic, 2012; Lopez and Jean-Marie, 2021; Williams, 2012). Concrete when ‘fresh’ can be moved around with a shovel, but becomes hard once it sets, requiring a more powerful tool to pulverise it.…”
Section: Discussionmentioning
confidence: 99%
“…Although James 1 recognised the presence of racial stereotypes around him at school, he sounded happy about the recognition he got from the other students. His story, however, highlights the role in his school life of racial aggression, subtle or overt verbal or non-verbal signs, which are common place in educational settings (Kohli et al, 2017; Lopez and Jean-Marie, 2021). While some participants described shying away from racial stereotyping, others responded more confrontationally, yet others like James 1 seemed indifferent.…”
Section: Research Findingsmentioning
confidence: 99%
“…The myriad of harmful effects caused by anti-Black racism cannot be overstated -it includes disparities in physical health and mortality (e.g., the death rate for Blacks/African Americans is generally higher than Whites for heart diseases, stroke, cancer, asthma, influenza, pneumonia, diabetes, HIV/AIDS, and homicide; Kochanek et al, 2020; see also : Cobbinah & Lewis, 2018;Feagin & Bennefield, 2014;Paradies et al, 2015), psychological wellbeing (for systematic reviews, see David et al, 2019 andKirkinis et al, 2018), education (e.g., Carter & Welner, 2013;Ladson-Billings, 2006;Lopez, & Jean-Marie, 2021;Milner, 2012), economic opportunity (e.g., the 2019 U.S. Census Bureau reported that 21.2 percent of non-Hispanic Blacks in comparison to 9.0 percent of non-Hispanic Whites were living at the poverty level; Kochanek et al, 2020), and rights of equality, essentially disadvantaging Blacks/African-Americans across every sector of life and society (e.g. Blackmon, 2009;Brondolo et al, 2009;Ruef & Fletcher, 2003).…”
Section: A Dialectical View On Fighting Racism With Dbtmentioning
confidence: 99%